1995
DOI: 10.1103/physrevc.52.1792
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime measurements inXe120

Abstract: Lifetimes for the lowest three transitions in the nucleus ' Xe have been measured using the recoil distance technique. Our data indicate that the lifetime for the 2, + -+0, + transition is more than a factor of 2 lower than the previously adopted value and is in agreement with more recent measurements performed on this nucleus.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…This ratio is an indicator of the amount of collectivity present in a particular nuclear configuration and shows that for N < 63 the νh 11/2 bands may exhibit a larger degree of collective behavior than the analogous transitions in the ground-state sequences of the even-mass isotopes. This [43], as well as the well established B(E2; 2 + → 0 + ) values in the most neutron-deficient even-mass xenon isotopes [33][34][35]. The B(E2) value for 119 Xe appears to reproduce the trend observed in the excitation energy ratios, where the inferred deformation is predicted to be similar between the two bands around A = 119.…”
Section: A the νH 11/2 Isomeric Statesupporting
confidence: 66%
See 2 more Smart Citations
“…This ratio is an indicator of the amount of collectivity present in a particular nuclear configuration and shows that for N < 63 the νh 11/2 bands may exhibit a larger degree of collective behavior than the analogous transitions in the ground-state sequences of the even-mass isotopes. This [43], as well as the well established B(E2; 2 + → 0 + ) values in the most neutron-deficient even-mass xenon isotopes [33][34][35]. The B(E2) value for 119 Xe appears to reproduce the trend observed in the excitation energy ratios, where the inferred deformation is predicted to be similar between the two bands around A = 119.…”
Section: A the νH 11/2 Isomeric Statesupporting
confidence: 66%
“…The lifetimes of the first excited states in the even-mass neutron-deficient xenon isotopes are well established for N > 58 [33][34][35][36]. The B(E2) values derived from these measurements reveal a large increase in deformation compared with B(E2) measurements in the ground-state sequences of both the neutron-deficient tellurium and tin isotopes, between 2 and 3 times larger.…”
Section: A the νH 11/2 Isomeric Statementioning
confidence: 89%
See 1 more Smart Citation
“…Summarized in figure 1 is the experimental data collected in the neutron-deficient lead region. A substantial amount of new information has been added or improved upon using various experimental techniques such as: decay studies [2][3][4][5][6][7][8][9][10][11], optical spectroscopy studies [12][13][14][15][16][17][18][19][20], recoil-distance lifetime measurements [21][22][23][24][25][26][27][28][29][30][31][32][33][34] and in-beam γ-ray/electron spectroscopy [35][36][37][38][39][40][41][42][43]. The contribution to this issue by Julin et al [44] details the most recent status of the in-beam experimental studies performed at the accelerator laboratory of the University of Jyväskylä Finland.…”
Section: Introductionmentioning
confidence: 99%
“…Although the increase was qualitatively described by the proton-neutron interacting boson model(IBM-2), earlier experimental B(E2) values for midshell nuclei were smaller than those of the theoretical predictions, and it was suggested that the Pauli blocking effect had to be taken into account to explain the experimental data [1,3]. Recently, however, Walpe et al have performed a new measurement of the lifetime of the 2 + 1 state in 120 Xe, and reported that the experimental B(E2) values are well reproduced by IBM-2 without Pauli blocking effect [4].…”
mentioning
confidence: 99%